Pemberdayaan Masyarakat Desa Sebakung Jaya Melalui Pelatihan Fardhu Kifayah untuk Pengurusan Jenazah - Khojir, Khojir; Sabrina, Elsa; Syafaat, Muhammad Yoghi; Wulandari, Ririn Fairuz; Agustianingsih, Tri; Asmara, Tri; Dewi, Yasmin Aulia (SIMAS: Jurnal Pengabdian Masyarakat, 2025)
Abstract: The tradition of handling corpses is an important part of social and religious life in this village. However, demographic and structural changes in recent years have affected the community's ability to carry out corpse management duties. The main limitation is the number of individuals capable of carrying out this task, which only consists of three people with adequate knowledge and skills. To overcome this problem, UINSI KKN students have initiated the Fardhu Kifayah training program with the aim of empowering more community members to play a role in handling corpses. This program involves collaboration between village officials, local religious leaders and community institutions to increase community understanding and skills in managing corpses in accordance with religious principles. The training process includes activity planning, implementation and evaluation. The outcomes of this program include increasing participants' understanding, increasing active participation, improving the quality of corpse management, community independence in managing corpses, and the potential to become a model of best practice in empowering rural communities. Keywords : Community Empowerment, Funeral Management, Religious Practices Abstrak Tradisi pengurusan jenazah menjadi bagian penting dari kehidupan sosial dan agama di desa ini. Namun, perubahan demografis dan struktural dalam beberapa tahun terakhir telah memengaruhi kemampuan masyarakat untuk menjalankan tugas pengurusan jenazah. Keterbatasan utama adalah jumlah individu yang mampu melaksanakan tugas ini, yang hanya terdiri dari tiga orang dengan pengetahuan dan keterampilan memadai. Untuk mengatasi masalah ini, mahasiswa KKN UINSI telah menginisiasi program pelatihan Fardhu Kifayah dengan tujuan memberdayakan lebih banyak anggota masyarakat untuk berperan dalam pengurusan jenazah. Program ini melibatkan kolaborasi antara pihak desa, tokoh agama setempat, dan lembaga masyarakat untuk meningkatkan pemahaman dan keterampilan masyarakat dalam pengurusan jenazah sesuai dengan prinsip-prinsip agama. Proses pelatihan mencakup perencanaan kegiatan, implementasi, dan evaluasi. Hasil luaran dari program ini mencakup peningkatan pemahaman peserta, peningkatan partisipasi aktif, peningkatan kualitas pengurusan jenazah, kemandirian masyarakat dalam pengurusan jenazah, dan potensi menjadi model praktik terbaik dalam pemberdayaan masyarakat di pedesaan. Kata kunci : Pengelolaan Jenazah, Pemberdayaan Masyarakat, Praktik Keagamaan